EKOLOGI BUDAYA DAN TRADISI : HIDUP DI DALAM RUANG ARSITEKTUR MULTI ETNIS - Varianotto Sanjaya; Maria Veronica Gandha (Jurusan Arsitektur dan Perencanaan, 2021)
Humans are social creatures that are defined as living things that need the presence of other people directly or indirectly. Where as humans are creatures that couldn’t live alone and therefore, is in need of a second, third, or more individuals to carry out daily activities, which occur in succession, resulting in habits and become rules passed down from generation to generation to maintain the